Scendendo nella «fossa oscurissima». Disgusto e pietà nella rappresentazione del sottoproletariato in Il mare non bagna Napoli (Itinera, 2024)
There is a presence that runs through the heterogeneous yet related stories of Il mare non bagna Napoli (1953) by Anna Maria Ortese, the crowd, the squalid and hallucinated plebs, «carpet of flesh» – a typical presence in the narratives and iconography of the “great Neapolitan fresco”. The structuring of the work can be interpreted as a gradual descent into the «very dark pit» of the damned, which is accomplished in the catabasis that constitutes the heart of the book (the short story La città involontaria), before at- tempting – in the other half, the long story Il silenzio della ragione – an ascent, first and foremost topographical, towards the quarters of the Neapolitan intelligentsia, as an effort to reconstruct the causes of the post-war cultural programme failure. Ortese’s sensitivity in the representation of the miserable people would here come to crack, according to many critical judgments on the work, as if the “pity” commonly attributed to the author, almost a hallmark of her poetics, was reversed into an ill-concealed disgust towards the Neapol- itan underclass, on whose abjections the narrator’s gaze insists throughout the work. The contribution would like to analyze the ways in which the Neapolitan crowd is represented and the related deformation devices (animalization, multiplication) employed in the text; we would therefore like to investigate the ethical and aesthetic motives of an attitude that does not seem to be motivated so much by «ontological insecurity», the bourgeois fear of contagion (which La Capria speaks of in connection with Ortese’s controversial book); it is, more likely, the descending movement of a poetics that is at one with cognitive pathos, which touches on the great questions of good and evil.
Keywords: Ortese, Il mare non bagna Napoli, Naples, Plebs, Nature